TERRITORIAL DIFFERENTIATION OF INCOMES ADJUSTED FOR INFLATION - M. V. Moroshkina (Russian Journal of Economics and Law, 2017)
Objective: to analyze and evaluate the regional disparities of socio-economic development of the Russian regions in terms of income differentiation adjusted for the level of inflation.Methods: indicator by which to measure the level of regional growth heterogeneity is Gini coefficient, allowing to determine the degree of the Russian regions’ deviation from absolute equality. The unique feature of the author’s approach is the calculation and analysis of the Gini coefficient not only in current prices but also in comparable prices of 1991. Thus, the comparison of the Gini coefficient in terms of "per capita income" in the period from 1991 to 2013 in comparable and current prices allows to estimate the impact of changes in the prices level on the dynamics of regional development.Results: the article states that the regions differentiation by the level of economic development determines the necessity of considering this factor in economic policy areas. In these circumstances, the analysis of income differentiation of the Russian regions has to take the impact of inflation into account.The article reviews the Russian and foreign research in the sphere of the income differentiation. Significant scientific interest to the problem of regional inequality is obvious over the past several decades. Approaches and methods of assessing the level of regional disparities are systematized, as well as its key performance indicators.To assess the level of differentiation of Russian regions, we used the Gini coefficient, which was calculated not only by current, but also by comparable prices. The calculation was carried out basing on the recalculation of the per capita income using the consumer price index. In the framework of the analysis, the calculated Gini coefficient for per capita income by current and integrated prices allowed to observe the differential behavior of this indicator. In terms of "per capita income" by current prices, there is a strong tendency of divergence between the regions. This dynamics can be explained by the differences in the level of prices in different Russian regions. The analysis of this indicator in comparable prices showed the opposite dynamics - the dynamics of convergence of the regions since 1999. During this period - the period of rising prices - we see the process of budgetary funds redistribution, which increases the income of the population employed in public-sector organizations. The income growth leads to convergence between the regions and to the reduced disparity.Scientific novelty: the article analyzes the dynamics of regional differences of the Russian regions in terms of "per capita incomes" in current and comparable prices, which allowed to assess the impact of inflation on this indicator in the period since 1991. Practical significance: the main provisions and conclusions of the article can be used in scientific and practical activities in addressing the issues of interregional differentiation. The results of the Gini index calculations by comparable prices of1991 are presented in a table and can be used in the analysis of interaction of macroeconomic indicators in the Russian regions and Russia as a whole.